Implementation of Information Technology Governance Based on CoBIT Framework 5. Case Study: Bureau of Information Systems & Technology-Buddhi Dharma University - Riki Riki (Tech-E, 2018)
The purpose of writing, to determine the level of capability in the Bureau of Information Systems & Technology at Buddhi Dharma University. Analyzing the achievement of its capability level and assisting BSTI in implementing international standardized IT governance. The methodology used is the CoBIT 5 framework as a measure of capability level guidance. The result is that the current level of BSTI capability is 2.027 which means at level 2 (managed process), the standard is at level 3. Conclusion that BSTI has been managed and implemented correctly, although the achievement of the level of capability is still in the middle position due to the lack of competition that forced Buddhi Dharma University to do business development.